Liberal environmentalism in international climate politics. An analysis of the discourses of Brazil and China within the framework of the Paris Agreement - Huwe de Paoli, Paola (2025)
This article investigates how liberal environmentalism appears in Brazilian and Chinese discourses within the framework of the Paris Agreement, particularly in their Nationally Determined Contributions (NDCs). Data is collected from documentary and bibliographic sources, which include the NDCs of Brazil and China, as well as records of dialogues, negotiations, agreements, and rules that shape international climate policy. Discourse analysis is employed as the technique for data analysis. It is emphasized that there are three political-ideological pillars that constitute liberal environmentalism—namely, sustainable development, the green economy, and carbon metrics—which guide the analysis of Brazilian and Chinese discourses. The study finds that both Brazil and China present climate change mitigation goals that are primarily oriented toward preserving the logic of capital, as opposed to safeguarding the Earth System inhabited by the human species and other living beings.